Vehicle headway distribution modelling of free-flowing traffic on two-lane single carriageways (2015)
Studies on vehicle headways are employed to understand traffic flow on highways. We model the vehicle headway distributions on a two-lane single carriageway in Ibadan, Nigeria. The Headway Generation Algorithm (THEGA) was developed to generate theoretical values for headway distribution modelling. Headway data for model calibration and validation were collected along Ibadan-Abeokuta Road for five days in April 2008 using a video camera. The generated headways fitted hyperbolic distribution models, and a spreadsheet of cumulative headway distribution was developed for a user-specified volume for flows ranging from 700 to 1000 vehicles per hour (vph). The results associated long headways with low flows, which reduced to short headways as flows increased and random arrival of vehicles changed to a car-following system. The validation of results with the Kolmogorov–Smirnov goodness-of-fit test at 0.01 significance level indicated good fits for the range of observed traffic volumes. The algorithm developed can be used to simulate traffic flows on two-lane single carriageways with the overall goal of efficient and effective traffic management of highway systems